Hazards of diisobutyl phthalate (DIBP) exposure: A systematic review of animal toxicology studies. (April 2019) - Yost, Erin E.; Euling, Susan Y.; Weaver, James A.; Beverly, Brandiese E.J.; Keshava, Nagalakshmi; Mudipalli, Anuradha; Arzuaga, Xabier; Blessinger, Todd; Dishaw, Laura; Hotchkiss, Andrew; Makris, Susan L.
Abstract: Background: Biomonitoring studies indicate a trend towards increased human exposure to diisobutyl phthalate (DIBP), a replacement for dibutyl phthalate (DBP). Recent reviews have found DIBP to be a male reproductive toxicant, but have not evaluated other hazards of DIBP exposure. Objective: To inform chemical risk assessment, we performed a systematic review to identify and characterize outcomes within six broad hazard categories (male reproductive, female reproductive, developmental, liver, kidney, and cancer) following exposure of nonhuman mammalian animals to DIBP or the primary metabolite, monoisobutyl phthalate (MIBP). Methods: A literature search was conducted in four online scientific databases [PubMed, Web of Science, Toxline, and Toxic Substances Control Act Test Submissions 2.0 (TSCATS2)], and augmented by review of regulatory sources as well as forward and backward searches. Studies were identified for inclusion based on defined PECO (Population, Exposure, Comparator, Outcome) criteria. Studies were evaluated using criteria defined a priori for reporting quality, risk of bias, and sensitivity using a domain-based approach. Evidence was synthesized by outcome and life stage of exposure, and strength of evidence was summarized into categories of robust, moderate, slight, indeterminate, or compelling evidence of no effect, using a structured framework. Results: Nineteen toxicological studies in rats or mice met the inclusion criteria. There was robust evidence that DIBP causes male reproductive toxicity. Male rats and mice exposed to DIBP during gestation had decreased testosterone and adverse effects on sperm or testicular histology, with additional phthalate syndrome effects observed in male rats. There was also evidence of androgen-dependent and -independent male reproductive effects in rats and mice following peripubertal or young adult exposure to DIBP or MIBP, but confidence was reduced because of concerns over risk of bias and sensitivity in the available studies. There was also robust evidence that DIBP causes developmental toxicity; specifically, increased post-implantation loss and decreased pre- and postnatal growth. For other hazards, evidence was limited by the small number of studies, experimental designs that were suboptimal for evaluating outcomes, and study evaluation concerns such as incomplete reporting of methods and results. There was slight evidence for female reproductive toxicity and effects on liver, and indeterminate evidence for effects on kidney and cancer. Conclusion: Results support DIBP as a children's health concern and indicate that male reproductive and developmental toxicities are hazards of DIBP exposure, with some evidence for female reproductive and liver toxicity. Data gaps include the need for more studies on male reproductive effects following postnatal and adult exposure, and studies to characterize potential hormonal mechanisms in females. Highlights: Gestational exposure in rat and mouse studies led to permanent adverse reproductive effects in males. Females had slight evidence of adverse reproductive effects, although data were sparse. Fetal resorptions and the observed male and female reproductive outcomes may share similar modes of action. Liver weights were increased, but interpretation of this effect was limited by absence of histological or biochemical data.